Targeting efficiency of nanoliposomes on atherosclerotic foam cells: polyethylene glycol-to-ligand ratio effects. (2nd August 2020) - Darwitan, Anastasia; Tan, Yang Fei; Wong, Yee Shan; Nedumaran, Anu Maashaa; Czarny, Bertrand; Venkatraman, Subbu
ABSTRACT: Background: Nanoparticles that actively target tissues, with ligands attached at the extremity of polyethylene glycol (PEG) spacer, are a promising strategy to enhance target cell specificity and internalization. However, the interplay between the targeting ligands and the adjacent ligand-free PEG remains poorly understood. Research design and methods: Experimentally, liposomes containing active folate ligands were firstly formulated and the optimum amount of ligand that yields the highest foam cell uptake was determined. Subsequently, ligand-free PEG was incorporated, and the effects of PEG lengths and concentrations on foam cell uptake were evaluated after the nanoparticles were incubated in human serum for 90 min. Results: It was demonstrated that the targeting efficiency progressively decreased and was eventually annulled as PEG-to-ligand ratio was increased, with loss of targeting effect occurring at PEG-to-ligand ratio of >2 for PEG 750, >0.5 for PEG 2000 and <0.5 for PEG 5000. Conclusions: This work demonstrates that PEG-to-ligand ratio and serum coating on nanoparticle surface are both important features to be considered in the design of active targeting nanocarriers. This work also supports the development of novel active targeting nanotherapies for atherosclerosis.